Trains in American Literature: Frank Norris and Jack Kerouac - Kopp, Lukáš (Univerzita Pardubice, 2019)
This bachelor thesis discusses the picture of trains in the selected works of Frank Norris and Jack Kerouac. First, the paper provides the theoretical background by describing the history of railways in the United States and its depiction in literature. Then, the selected authors and texts are analyzed concerning different literature and socio-historical contexts. The conclusion on the decisive motives leading both authors to contradictory picture of trains is made at the end of the thesis.
Vlaky v americké literatuře: Frank Norris a Jack Kerouac
Keywords: vlaky; Norris, Frank; Kerouac, Jack; USA; literatura; trains; Norris, Frank; Kerouac, Jack; USA; literature